Implementasi Five Moment Hand Hygiene Pada Perawat Di Ruang Rawat Medikal Bedah Rumah Sakit Santa Elisabeth Medan - Cindy Clara Sinaga; Lili Suryani Tumanggor; Samfriati Sinurat (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
The prevalence of nosocomial infections worldwide has become a serious concern for healthcare professionals, especially in hospitals. One contributing factor is the inadequate implementation of the five moments hand hygiene in handwashing procedures that do not conform to operational procedure standards. The aim of this research is to determine how the implementation of the five moments hand hygiene among nurses in the surgical medical care ward at Santa Elisabeth Hospital in Medan. This study utilized a descriptive cross-sectional approach, employing observation sheets. The sample size included 30 nurses in the Surgical Medical Care Ward at Santa Elisabeth Hospital in Medan, using total sampling technique. The measurement tool was an observation sheet, and the data analysis employed univariate analysis. The research findings revealed that, in the first moment before patient contact, 56.7% of nurses did not adhere to the practice, while 43.3% did. In the second moment, before aseptic procedures, 56.7% of nurses did not comply, and 43.3% did. In the third moment, after exposure to patient body fluids, all nurses (100%) adhered to the practice. In the fourth moment, after patient contact, all nurses (100%) complied. In the fifth moment, after contact with the patient's environment, all nurses (100%) followed the practice. It is hoped that nurses can consistently implement the five moments hand hygiene to prevent disease transmission and nosocomial infections, fostering a habit of incorporating these practices into nosocomial infection prevention.